(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine the features of the microstructure of choreoretinal complex in rats with diabetes induced by streptozotocin in the presence of axial myopia. Material and Methods: Fifty-five Wistar rats (110 eyes; age, 2 weeks to 14 weeks) were used in experiments. Four groups were formed: group 1 (axial myopia only); group 2 (diabetes only); group 3 (both myopia and diabetes); and group 4 (controls; intact animals). High form-deprivation myopia was produced in two-week animals by surgically fusing the eyelids of both eyes and these animals were maintained under conditions of reduced illumination for two weeks to induce a more intense myopization of the globe. Eyelid sutures were removed on completion of these two weeks. Two weeks thereafter, type 2 diabetes mellitus was induced in rats with induced axial myopia and intact rats. A 50 mg/kg intraperitoneal streptozotocin injection for 5 days was used for this purpose. Elongated axial length and increased anterior chamber depth as measured by in vivo ultrasound were an objective criterion of the development of myopia in experimental animals. A glucose level of ≥ 4.5 mmol/L was a criterion of the development of diabetes. Two months after inducing diabetes, 14-week rats were sacrificed, and their eye tissue samples were processed by a routine method and assessed by electron microscopy. Ultrastructure of the choroid, RPE, and retinal photoreceptor cells were examined. Ultra-thin sections were cut, stained with lead citrate according to the procedure described by Reynolds, and observed with a PEM-100-01 Transmission Electron Microscope. Results: Our ultrastructural study found that myopization of the rat globe with elongation of the axial length somewhat reduced the severity of some ultrastructural changes in the choreoretinal complex in induced type 2 diabetes due to reduced choroidal swelling and dominance of compensatory processes with increased energy producing, protein synthesis and other functions in the endothelial vessels and choriocapillaries as well as RPE cells. Out findings seem to corroborate the concept that myopized eyes have capacity to somewhat buffer the development of severe diabetic retinopathy, likely due to some compensatory-and-restorative processes.